Low albumin-to-creatinine ratio: a novel predictor of 90-day mortality in hepatocellular carcinoma with liver cirrhosis - Pamungkas, Kadek Mercu Narapati; Dewi, Putu Itta Sandi Lesmana; Dewi, Ni Luh Putu Yunia; Dewi, Ni Nyoman Gita Kharisma; Sindhughosa, Dwijo Anargha; Mariadi, I Ketut (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundDespite recent advances in the treatments of hepatocellular carcinoma (HCC), the prognosis of HCC patients remains controversial. Lowered serum albumin in hepatocellular carcinoma, an advanced stage of liver cirrhosis, indicates a worsening condition. Hepatorenal syndrome, marked by increased serum creatinine, is a key mortality indicator. The aim of this study was to determine the serum albumin-to-creatinine ratio (sACR) as a predictor of mortality in patients with HCC and liver cirrhosis. MethodsThis retrospective cohort study included 37 patients with HCC and liver cirrhosis. Patient characteristics, sACR, model of end-stage liver disease (MELD) score, and Child-Turcotte-Pugh (CTP) score were obtained from medical records. The optimal cut-off point for the sACR was determined using receiver operating characteristic (ROC) analysis to evaluate its predictive ability for 90-day mortality. Survival analysis was conducted using the Kaplan-Meier method with a log-rank test, and Cox regression was employed to obtain hazard ratios (HR) to estimate the patient’s prognosis. ResultsA low sACR cut-off of 2.32 was identified. Kaplan-Meier analysis confirmed that sACR met the proportional hazard assumption. sACR <2.32 was a significant predictor of 90-day mortality (HR 6.52; 95% CI 1.80-23.63; p=0.004), comparable to MELD 40 (HR 41.3; 95% CI 1.98-862.90; p=0.016) and CTP category (HR =2.19;95%CI: 0.79-6.06;p=0.131). Conclusion The sACR is a novel predictor of 90-day mortality in HCC patients with liver cirrhosis. Lower sACR is associated with overall survival and may help to design strategies to personalize management approaches among patients with HCC and liver cirrhosis.